Under Sundanese eyes; Raden Ajoe Abdoerachman’s journey to Europe - Kurnia, Atep (UI Scholars Hub, 2024)
This article examines the travel account written by Raden Ajoe Abdoerachman, the wife of a senior native official, the Regent of Meester Cornelis (Jatinegara), Raden Aria Abdoerachman, who, with his family, was sent at the expense of the colonial government to the Netherlands to study agricultural practices in 1928. The account shows the colonial subject’s admiration for and mimicry of European behaviour and practices, but occasional ironic comments show her ambivalence towards some institutions in the Netherlands while at the same time she also criticises unfair representations of Indonesia.